Uncommon Diverticular Disease - Mohanty, Sanjay; Webb, Shawn P. (Clinics in Colon and Rectal Surgery, 2018)
This article describes the epidemiology, pathogenesis, diagnosis, and treatment of three rare variants of diverticular disease: cecal and right-sided colonic diverticula, giant colonic diverticula, and small bowel diverticula.
Keywords: cecal diverticulosis; giant diverticula; small bowel diverticula